The Relationship Between Digital-Based Learning Management and The Quality of Education - Encu, Asep; Juliansyah, Dicky (Jurnal Isema : Islamic Educational Management, 2024)
The use of technology in education field, especially in student learning activity, began to be widely used after the Covid-19 pandemic. However, the use of technology in student learning often causes problems that can hinder the learning process. These problems include a poor internet network, limited digital learning facilities and inadequate teacher skills in using technology. Therefore, the importance of providing adequate facilities and training for educators is a priority to be realized. This research was carried out with the aim of finding out the relationship between digital-based learning management and the quality of education at MAN Bandung Regency. This research uses a quantitative approach with a correlational descriptive method. Research findings show that the correlation test results are 0.000 <0.05, which means that there is a significant relationship between the two variables. This research obtained a Pearson correlation value of 0.850, which has a (+) symbol and does not have a (-) symbol in the resulting value. So, the variables in this study have a unidirectional and very strong relationship because they are at the interval level of 0.80-1.00, It also means that the better the digital-based learning management, the better the quality of education. This research also obtained an R Square result of 0.722, which means that the relationship between digital-based learning management and education quality is 72.2% and the remaining 27.8% is influenced by other factors outside of this research.